Algorithmic aspects of cloud computing : first International Workshop, ALGOCLOUD 2015, Patras, Greece, September 14-15, 2015. Revised selected papers /: first International Workshop, ALGOCLOUD 2015, Patras, Greece, September 14-15, 2015. Revised selected papers. (2016) - Unknown
No abstract available